27.2k views
2 votes
I try solve and I no get correct answer! Please help I don’t know

I try solve and I no get correct answer! Please help I don’t know-example-1

1 Answer

5 votes

gof means that we must first evalute f at x and next evalute the result in g.

In our case,


\text{gof(x)}=g(f(x))

By taking into account that f(x)=3x-1 and g(x)=4x^2+9, we have


\begin{gathered} (\text{gof)(x)}=g(f(x)=g(3x-1)=4(3x-1)^2+9 \\ \end{gathered}

In summary,


(\text{gof)(x)}=4(3x-1)^2+9

Now, we must substitute x=-2 in this lat equation, It yields


(\text{gof)(-}2)=4(3(-2)-1)^2+9

hence, we obtain,


\begin{gathered} (\text{gof)(-}2)=4(-6-1)^2+9 \\ (\text{gof)(-}2)=4(-7)^2+9 \\ (\text{gof)(-}2)=4\cdot49+9 \\ (\text{gof)(-}2)=196+9 \\ (\text{gof)(-}2)=205 \end{gathered}

Hence, the answer is 205

User Rhodope
by
6.4k points